On the unstabilized genus name for the Nearctic greater fritillaries (Lepidoptera: Nymphalidae: Argynnini) - Pfeiler, Edward (Zootaxa, 2026)
There is current disagreement among researchers on whether the Nearctic greater fritillaries, a group that includes several endangered and threatened species, should remain in the genus Speyeria Scudder—in use for 80 years—or be placed as a subgenus of the Palearctic Argynnis Fabricius. A review of the recent scientific literature covering this group revealed the extent of this controversy in that only about half of the articles consulted recognized Speyeria as a subgenus of Argynnis. A summary of molecular phylogenetic studies using a variety of genetic markers provides a possible explanation for why this taxonomic change is controversial. These studies confirmed that species assigned to Speyeria, although generally morphologically similar to Argynnis, form a monophyletic group, a widely-accepted criterion for generic status. Thus, the controversy centers mainly on (1) the issue of taxonomic stability of a long-accepted genus name, (2) the need for increased taxon sampling of Palearctic taxa in phylogenomic studies, and (3) whether genetic divergence thresholds, including those of DNA barcodes analyzed here, can confidently be used as an aid in delimiting genera in the greater fritillaries. Based on the evidence presented here it is proposed that Speyeria be reinstated to full genus status.